Effect of plastic accumulation on the nucleation of cracks in railroad rails due to bidirectional loaded traffic - Reis, Thairon; de Abreu Lima, Eduardo; Bertelli, Felipe; Antunes dos Santos Junior, Auteliano (International journal of fatigue, 2018)
•Reversing the direction of traffic in heavy-haul railroads can cause additional plastic deformation in already plastically deformed rails.•Additional plastic accumulation in rails does not cause significant alteration in the life of rails to shelling.•Shakedown limit is reached after a few loading cycles on rails for heavy-haul traffic.•Life estimation for rails using the multiaxial fatigue approach is consistent with service data for heavy-haul railroads. Bidirectional loaded traffic effect was investigated for heavy haul railway lines, using a coupled analytical and numerical method. A tridimensional elastoplastic finite element model of a rail was developed to obtain the stress and strain distributions. Hertz and Kalker theories were used to estimate the contact pressure and tangential forces on the wheel/rail surface. The resulting critical stress tensor was used to investigate the crack nucleation with Dang Van and Findley’s criteria. The results reveal that the plastic strains stabilize early, the resulting stress range is similar, and that the bidirectional loading affects the life to crack nucleation.